Meningkatkan Kemampuan Literasi Numerasi Dampak Belajar Daring Selama Pandemi di SD Negeri 066668, Medan Johor - Adinda Salsabillah; Sinaga, Randa Putra Kasea (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Literacy and numeracy means knowledge and intelligence to use various numbers and symbols related to basic mathematics to solve practical problems in everyday life and then analyze information displayed in various forms and interpret the results of the analysis to get results and make decisions (Kemdikbud in Mahmud & Pratiwi, 2019). Literacy and numeracy consist of three aspects such as counting, numeracy relations, and arithmetic operations (Purpura, 2009). As Covid-19 began to spread in Indonesia, the education system in Indonesia changed drastically. The announcement of Work From Home (WFH) which requires everything to be done from home including learning activities previously carried out at school to learning done at home. Online learning is learning centered on the students themselves as the main actors in learning, while the teacher acts as a facilitator and mediator in the learning process. The micro intervention implemented at SD Negeri 066668 Medan Johor is a form of individual assistance service to help students improve their literacy and numeracy skills. The method used is the casework method as stated by Skidmore, Thackeray, and Farley in Adi (2005: 149) as an effort to solve problems and find programs that suit the needs of students and schools. The method consists of the research stage, assessment stage, intervention stage, and termination stage.